(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Vikram Seth’s first novel The Golden Gate is novel, as in this is a fiction in section. Novel in stanza is a thing of novelty. In the on-going abstract history, novels in section have not showed up however Vikram Seth says he has drawn motivation from Alexander Puskin who has created Eugene Onegin, a novel in refrain. Seth’s The Golden Gate has every one of the fixings to be portrayed as an ’American novel’. It manages the way of life, culture and love of present America. Vikram Seth’s utilization of Realism and his social concerns are extraordinary with regard to different writers of Indian birthplace. Different ideas on Realism have used to examine his major anecdotal attempts to determine the highlights of authenticity under play in his books. By investigating real works in the pragmatist stream in Indian Fiction in English, a sincere endeavor have been made to stick point that, as a story procedure, authenticity prevails in every one of them. By his own story procedure and uniqueness of social concern, Seth has isolated himself out of the fleeting trend of other pragmatist writers and built up his noticeable quality over others as a noteworthy author of the subcontinent.